Jesus, the Kingdom and the Promised Land - Willitts, Joel (2015)
N.T. Wright’s understanding of the nature of the kingdom of God in Jesus’ proclamation has been persuasive and significant. The present article engages Wright’s presentation with respect to the particular question of the relationship to between the kingdom of God and Israel’s Land promise. For all the focus on the Jewish context of Jesus, the so-called Third Quest for the Historical Jesus, of which Wright is an exemplar, has been reluctant to consider the possibility of an ongoing interest in territorial restoration in Jesus’ conceptions of the eschatological hope. Where Wright does address the Land of Israel he argues that Jesus reinterprets it away from a localized territorial conception to a more universal symbol of God’s sovereign reign. The argument of the article, while appreciating much in Wright’s interpretation of Jesus, seeks to destabilize his ‘reinterpretation view’ of the Land, on the one hand. And, on the other, the present work presents substantial evidence in support of the hypothesis that the historical Jesus both affirmed Israel’s Land promise and promulgated Israel’s territorial restoration in his teaching, preaching, and even in his physical movements in Greater Galilee.
Keywords: Davidic Messianism -- Greater Galilee -- Israel -- Jesus -- kingdom of God -- Land of Israel -- Land-kingdom motif -- restoration -- the Twelve Disciples -- N.T. Wright